Development of pumpkin based pumpkin (Cucurbita spp.) (Research, Society and Development, 2019)
Biscuit is the product obtained by kneading and baking the dough prepared with flour, starch, fermented or not, and other food substances with functional properties that add value to the product. In recent years, the increase in the value of pumpkin (Cucurbita spp.) Due to health benefits, such as bioactive compounds and nutrients, has been reported in the prevention and treatment of diseases. The accomplishment of this study, had the objective to develop biscuit based on the pumpkin (Cucurbita spp). This is an experimental research carried out in the laboratories of Dietetic Technique and Sensory Analysis of Foods of the University Center of Science and Technology of Maranhão - UNIFACEMA, Caxias - MA. Three samples of biscuits were tested: sample A (without pumpkin), sample B (containing 25% pumpkin) and sample C (containing 50% pumpkin). For sensory evaluation, untrained assessors were invited to analyze the following parameters: appearance, texture, aroma, flavor and overall acceptance using a hedonic scale of 9 points, and the intention to purchase attribute using a hedonic scale of 5 points. Regarding the microbiological analysis, the quantification of coliform at 45 ºC and molds and yeasts was performed. The three samples were well accepted by the tasters for all the sensorial attributes, with greater acceptability of sample B. Therefore, the development of the pumpkin-based biscuit work stands out as a new alternative in the production of biscuit with possible functional properties, through the standardization of the stages of product elaboration, good sensorial acceptance and microbiological standards according to the current legislation.